2015
DOI: 10.1186/s13023-015-0371-1
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder in tuberous sclerosis complex: searching for risk markers

Abstract: BackgroundNeuropsychiatric disorders are present in up to 90 % of patients with Tuberous Sclerosis Complex (TSC), and represent an important issue for families. Autism Spectrum Disorder (ASD) is the most common neurobehavioral disease, affecting up to 61 % of patients. The aims of this study were: 1) to assess the prevalence of ASD in a TSC population; 2) to describe the severity of ASD; 3) to identify potential risk factors associated with the development of ASD in TSC patients.MethodsWe selected 42 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 29 publications
(40 reference statements)
2
50
1
3
Order By: Relevance
“…In other words, although the seizure type most likely to occur at seizure onset in our population was infantile spasms, we found that age at seizure onset exhibited greater impact on predicting developmental outcome. Our finding that timing of seizure onset is more significant than the presence or absence of infantile spasms differs from conclusions drawn by others [2, 10, 11, 15, 28]. For example, Jozwiak et al found that the presence of infantile spasms was associated with 3–4 times higher risk of moderate to profound delays independent of age of seizure onset [11].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In other words, although the seizure type most likely to occur at seizure onset in our population was infantile spasms, we found that age at seizure onset exhibited greater impact on predicting developmental outcome. Our finding that timing of seizure onset is more significant than the presence or absence of infantile spasms differs from conclusions drawn by others [2, 10, 11, 15, 28]. For example, Jozwiak et al found that the presence of infantile spasms was associated with 3–4 times higher risk of moderate to profound delays independent of age of seizure onset [11].…”
Section: Discussioncontrasting
confidence: 95%
“…Type and severity of seizures, especially infantile spasms, along with early age of seizure onset also appear to be associated with increased likelihood of cognitive and behavioral difficulties particularly if seizures are not controlled [812]. Similar associations have been reported for higher risk for ASD in TSC [9, 1315], and it has been suggested that epilepsy may be an independent predictor of intellectual ability in TSC [7, 10, 16]. At this time, it is unclear as to whether neurodevelopmental disorders are caused by the underlying brain abnormalities seen in TSC, subsequent development of epilepsy, or both [17].…”
Section: Introductionmentioning
confidence: 83%
“…This equal gender distribution has also been reported in previous studies assessing the prevalence of ASD in TSC 24,25 .…”
Section: Discussionsupporting
confidence: 86%
“…Neurodevelopmental or neuropsychiatric disorders (referred to as TSC‐associated neuropsychiatric disorders); [de Vries et al, ; Leclezio, Jansen, Whittemore, & de Vries, ] are common. About 25–60% of children with TSC will receive a diagnosis of Autism Spectrum Disorder (ASD) [Capal et al, ; Granader et al, ; Jeste, Sahin, Bolton, Ploubidis, & Humphrey, ; Vignoli et al, ], and more than 50% have some degree of cognitive impairment [Curatolo, Moavero, & de Vries, ; Joinson et al, ].…”
Section: Introductionmentioning
confidence: 99%